2021
DOI: 10.1111/jfpe.13789
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of liquid nitrogen freezing in long‐term frozen preservation of hairtail (Trichiurus haumela): Enzyme activity, protein structure, and tissue structure

Abstract: This study aimed to investigate the effects of liquid nitrogen freezing (LNF) in long‐term frozen preservation of hairtail. Fresh hairtail was frozen by liquid nitrogen or cold air and stored at −20°C or −80°C for up to 120 days. The contents of carbonyl, TCA‐soluble peptides, AG and NAG enzyme activities increased, whereas Ca2+‐ATPase, Mg2+‐ATPase activity and the contents of sulfhydryl group decreased with the storage time increased. The activities of cathepsin B and B + L could be inhibited by low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 55 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Amino acids such as lysine, proline, and arginine are easily oxidized into semialdehyde under the action of reactive oxygen species and metal ions, accounting for most of the total carbonyl contents ( Li et al, 2021 ). Hu et al (2021) discovered that the carbonyl content of hairtail MP had an increase after liquid nitrogen quick-freezing, confirming the oxidation of frozen fish protein. The carbonyl content of IF was higher than that of UAF samples significantly.…”
Section: Resultsmentioning
confidence: 94%
“…Amino acids such as lysine, proline, and arginine are easily oxidized into semialdehyde under the action of reactive oxygen species and metal ions, accounting for most of the total carbonyl contents ( Li et al, 2021 ). Hu et al (2021) discovered that the carbonyl content of hairtail MP had an increase after liquid nitrogen quick-freezing, confirming the oxidation of frozen fish protein. The carbonyl content of IF was higher than that of UAF samples significantly.…”
Section: Resultsmentioning
confidence: 94%
“…The reversibility of all freeze–thawed cheeses is significantly lower than the fresh cheese due to the different degrees of damage and the low-temperature denaturation of protein. Studies have shown that ultra-low-temperature freezing can change the secondary and tertiary structure of a protein, and then affect the quality of fish [ 19 ]. Generally speaking, the stronger the structural integrity, the higher the recovery.…”
Section: Resultsmentioning
confidence: 99%
“…During storage, the values of the TPA results decreased. This might be because the TPA could be related to the diameter of muscle fibers and the contents of free water and myofibril attachment [61]. From the results, we could observe that during the early stage, the declining rate of all groups was slow, especially for hardness, and the rate decreased rapidly with a longer time.…”
Section: Texture Profile Analysismentioning
confidence: 85%